(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Forensic analysis of volatile memory plays a crucial role in cyber crime investigation. It has been observed that when available, RAM dump helps forensic investigators in retrieving many useful information related to a crime. There are variety of tools available for RAM analysis including Volatility, which currently dominates open source RAM forensic tools. It has been experienced that many times forensic investigators do not think possibilities of having a malware in the RAM dump. And, if it is there, still they are not very expert Malware Analysts, so it becomes difficult for them to analyze possible malware in a RAM dump. Availability of tools like Volatility lets forensic investigators identify and correlate various components to conclude whether the crime was carried out using any malware or not. However, use of volatility requires knowledge of command line tool and dynamic as well as static malware analysis. This work is done to assist forensic investigators in detecting and analyzing possible malware from a RAM dump. The work is based on volatility framework and outcome is a single step automated tool which analyzes RAM dump and possible malware residing in that. Final report generated using this tool gives accurate details about possibilities of use of malware in committing a crime.